Analysis of improving innovative work behaviour of vocational high school teachers in terms of servant leadership with knowledge sharing as an intervening variable - Hendro Prasetyono; Sumaryati Tjitrosumarto; J. Sabas Setyohadi; Sri Hapsari; Ira Pratiwi Ramdayana (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
The purpose of this research is to describe the innovative work behavior of vocational high school teachers in terms of servant leadership which is intervened by knowledge sharing. This research uses a quantitative approach with a survey method. The sampling technique was simple random sampling which came from vocational high school teachers from the provinces of East Java, Central Java, West Java, DKI Jakarta, Banten, Riau Islands, and South Sumatra with a total of 165 teachers. Data analysis techniques using descriptive analysis and path analysis. Results: The dimension of the teacher's innovative work behavior, namely with the intent of benefit to the organization has the highest score and the idea promotion dimension has the lowest score. Servant leadership has a positive and significant influence on knowledge sharing with a contribution of 42.3%. knowledge sharing has a positive and significant influence on innovative work behavior with a contribution of 58.4%. Knowledge sharing cannot be an intervening variable of servant leadership on innovative work behavior because the path analysis results show that servant leadership does not directly affect innovative work behavior through knowledge sharing. The implication is that city or district education offices must further enhance the idea promotion exploration of teachers through training or workshops and maintain that with the intent of benefit to the organization of teachers through servant leadership style and knowledge sharing of teachers and school principals.